THE INFLUENCE OF ASSET GROWTH, TOTAL DEBT TO ASSET AND RETURN: ON INVESTMENT SHARES OF SYSTEMATIC RISK IN CONSTRUCTION SECTOR IN BEI - Kennedy, Posma Sariguna Johnson; Pratama, Bernadt Andri (Universitas Kristen Indonesia, 2017)
This study aims to determine the extent of the effect of asset growth, total assets Debt and Return on investment against systematic risk (beta stocks) at a construction company in the Stock Exchange 2012-2016 period. The data used for this study quantitative data. The data used in the annual financial statements of the six companies the construction sector in Indonesia Stock Exchange during the five years, the data on monthly stock price that is processed by investigators into the share price per year. All data used in this research is secondary data obtained from www.idx.com and www.yahoofinance.co.id. This research method of data used in this study are all measured by using a ratio scale measurements showed that the absolute value of an object. The results of this study indicate that the value of the coefficient of determination (Adjusted R2) is approximately 0.428. This means that the variance beta stocks can be explained by the variance Asset growth, Debt to Total Assets, Return on investment can be explained beta stocks by 42.8%, while the remaining 57.2% is explained by other factors besides the variables studied. F count that variable Asset growth, debt to total assets and the return on investment influence simultaneously toward Beta Shares. Individual Asset ratios Return on investment growth and a positive effect on beta stocks while the ratio of debt to total assets negative effect on beta stocks and the only variable Asset growth and return on investment that are statistically significant.Keywords: :Asset Growth, Debt to Total Asset , Return On Invesment and Beta Stock.